Trabalho feminino em contexto angolano: um possível caminho na construção de autonomia - Lopes, Claudio Bartolomeu (2010)
The present dissertation tries to show how the Angolan women, especially from the Bié Province, taken possession of their work as a form of to build possible ways that could strengthen their fight to get autonomy. The research was carried out at the Kuito town and counted with eleven workers women participation, subject of this research that through their own experiences contributed for the understanding of the complex world of the gender relationship, in an African context, strongly marked for patriarchal influences and African culture. Was adopted the oral history methodology, where through interactive dialogues with the women could understand how they see and react at the oppression, exploration and discrimination situations that them are frequently victims, and how the pathway they take to go beyond of this problematic. This dissertation shows, on own women speaking the alternatives that they conceive to be the possibilities to build autonomy, as education and work access and political participation